Nasal-nanotechnology: revolution for efficient therapeutics delivery. (23rd March 2016) - Kumar, Amrish; Pandey, Aditya Nath; Jain, Sunil Kumar
Abstract: Context : In recent years, nanotechnology-based delivery systems have gained interest to overcome the problems of restricted absorption of therapeutic agents from the nasal cavity, depending upon the physicochemical properties of the drug and physiological properties of the human nose. Objective : The well-tolerated and non-invasive nasal drug delivery when combined with the nanotechnology-based novel formulations and carriers, opens the way for the effective systemic and brain targeting delivery of various therapeutic agents. To accomplish competent drug delivery, it is imperative to recognize the interactions among the nanomaterials and the nasal biological environment, targeting cell-surface receptors, drug release, multiple drug administration, stability of therapeutic agents and molecular mechanisms of cell signaling involved in patho-biology of the disease under consideration. Methods : Quite a few systems have been successfully formulated using nanomaterials for intranasal (IN) delivery. Carbon nanotubes (CNTs), chitosan, polylactic-co-glycolic acid (PLGA) and PLGA-based nanosystems have also been studied in vitro and in vivo for the delivery of several therapeutic agents which shown promising concentrations in the brain after nasal administration. Results and conclusion : The use of nanomaterials including peptide-based nanotubes and nanogels (NGs) for vaccine delivery via nasal route is a new approach to control the disease progression. In this review, the recent developments in nanotechnology utilized for nasal drug delivery have been discussed.